Answer:
8y^3+6y^2-29y+15
Step-by-step explanation:
the correct expression is
(4y − 3)(2y^2 + 3y − 5)
Given data
We have the expression
(4y − 3)(2y^2 + 3y − 5)
let us open bracket
8y^3+12y^2-20y-6y^2-9y+15
Collect like terms
8y^3+12y^2-6y^2-20y-9y+15
8y^3+6y^2-29y+15
A(-8,0) B(-12,12)the center is w((-8-12)/2 , (0+12)/2)....(midel [ AB]w(-10 ,6)the ridus is : r = AB/2AB = √(-12+8)²+(12-0)² = √16+144 =√160/2an equation in standard form equation of the circle :(x+10)²+(y-6)² = (√160/2)²=160/4 = 40
Answer:
D.
Step-by-step explanation:
That would be D because there is a repetition of x = -6.
-6 maps to -6, 5 and -5 which is not allowed in a function.
Functions can be one-to-one or many-to-one but not one-to-many.